Pengaruh Supervisi Akademik, Kompetensi Guru, Motivasi Kerja Guru, dan Lingkungan Kerja Guru terhadap Kinerja Guru SMAN 7 Kota Kupang - Agatha Sulla, Angelica; Ola Langoday, Thomas; Ruminah, Ruminah; H. Kaluge, Agapitus; Man, Stanis (Jurnal Ilmu Manajemen Terapan, 2023)
Teacher performance is the level of success a person shows through workability in achieving a set goal. To measure the teacher’s performance could be viewed from academic supervision, teacher competence, teacher’s motivation and teacher’s working environment. The results of descriptive statistical analysis show that teachers of SMA N 7 Kota Kupang's perception of academic supervision is in a good category (79), teacher competency is excellent (84), teacher job motivation is excellent (80), and teacher working environment (73). The results of inferential statistical analysis show academic supervision has a positive effect on teacher performance (3.934 > 2,) with significance (0,000 < 0,05); teacher competence had positive impact on teacher performance (0,836) and insignificance (0,341 > 0,05); teacher job motivation had no effect on teacher performance (0.610 < 2,306) with insignificance (0,543 > 0,05); teachers' work environment had no effect on teachers' performance (1.275 < 2,306) and was not significant for teacher performance (0,036 > 0,05). Simultaneous academic supervision, teacher competence, job motivation, and teacher working environment affected teacher performance (14,410 >2,306) with significance (0,000 < 0,05). The contribution of academic supervision, teacher competence, job motivation, and teacher working environment is 35% in comparison the remaining 65% is contributed by other factors that are not included in this study.